'It's normal to have damp': Using a qualitative psychological approach to analyse the lived experience of energy vulnerability among young adult households. Issue 7 (August 2017) - Butler, Danielle; Sherriff, Graeme
Seeking to promote methodological innovation in fuel poverty research, this paper reflects on the use of a novel qualitative psychological approach known as interpretative phenomenological analysis. The benefits and limitations of this methodological approach are discussed within a detailed account of findings from a small-scale study undertaken in Salford, UK. Contributing to an existing gap in the existing evidence base, the research focused on the lived experience of young adult households: a demographic group identified as being disproportionately more likely to be living in fuel poverty compared to any other age group. Three emergent themes were identified: 'establishing the independent home', 'threats to home comfort' and 'energy and coping'. Multiple references to conditions typical of fuel poverty were disclosed, such as: self-disconnection, energy debts, cold homes and unrelenting challenges with damp and laundry practices. 'Vulnerability' mostly consumed narratives of past experience, with participants discussing the present and future with positive affectivity. Implications for further research are explored, including the potential to more effectively target support by reframing current discourse away from one centred on 'vulnerability'.